Power and Virtue in Elkanah Settle's Ibrahim - Mohammad Ahmed Rawashdeh (Miscelánea: A Journal of English and American Studies, 2014)
Throughout the Medieval and Renaissance periods, British literary works concerned with the Orient served to underpin negative opinions about the people, and particularly the rulers, of the region. One might have expected the significant social, political and religious changes that were brought about by the Civil Wars and the Enlightenment to have altered that trend. However, uncomplimentary aspects of Middle Eastern life, as it was understood by Western writers, continued to circulate during the Restoration and eighteenth century. One writer stands out among the playwrights and authors of the period. In contrast to his contemporaries, Elkanah Settle extends the impact of the prevailing positive atmosphere beyond the shores of Britain and projects it into the Orient. In his play Ibrahim, Settle presents an Oriental ruler who shows true merit in his character, rather than the usual despotic and dictatorial traits adhered to in other plays of the genre. The ruler, Solyman, possesses a level of virtue which makes his family members and his subjects alike admire him and even allows them to criticize, and even rebuke him, when he deviates from the path of honor and virtue. Solyman has wisdom enough to seek advice, accept criticism, admit his weakness and try to redress the injuries he has caused to others by his recklessness. These are rare abilities among the rulers portrayed in Oriental plays of the period. The aim of this article is, therefore, to affirm how Settle, as a writer of a particular genre at a particular point in history, differs greatly from his contemporaries, apparently showing a much more positive face to life in the Orient